Cultural memory studies an introduction - Pethes, Nicolas 1970- (Cambridge Scholars Publishing, 2019)
This volume provides an overview of theories of cultural memory that are intensively discussed in cultural studies and humanities disciplines such as history, sociology, literary studies, art history, and media studies. Cultural memory encompasses all rituals, institutions and practices through which communities establish their identity and common origin, which are challenged by the digital turn today. The book presents, on the one hand, basic arguments by the most important memory theorists of the 20th and 21st centuries and, on the other, exemplary descriptions of the most significant forms
Keywords: Collective memory / Philosophy; Culture; Memory / Cross-cultural studies; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; Memory; Electronic books; Cross-cultural studies